Pengelolaan Supervisi Klinis Di SMK N 1 Karangayar Tahun 2013/2014 - SUKARNO, Aris, Prof. Dr. Yetty Sardjono, M.Si, Drs. Budi Sutrisno, M.Pd (2015)
The aim of this study were: (1) Describe the planning of clinical supervision in SMK 1 Karanganyar; (2) Describe the implementation of clinical supervision in SMK 1 Karanganyar; and (3) Describe the clinical follow-up supervision in SMK 1 Karangayar. This research is qualitative research. Objects in this study is the planning, execution, and follow-up clinical supervision in SMK 1 Karangayar. The data of this study documents the results of interviews supported with photos as well as teachers and adminitarasi administrative supervision. Data collected by observation, interview, and documentation. Clinical supervision Planning Head of SMK N 1 Karanganyar already involve teachers of SMK N 1 Karanganyar actively and openly. In the planning of clinical supervision Head of SMK N 1 Karanganyar have applied the analysis 5 W + 1 H. Implementation of clinical supervision by the Head of SMK N 1 Karanganyar can change the behavior of the teacher teaching. Teachers have made a new learning tools and begin implementing cooperative learning methods and contextual, as well as utilizing instructional media and laboratories in the Head SMK N 1 Karanganyar. Follow-up clinical supervision by the Head of SMK N 1 Karanganyar focuses on improving the professional competence of teachers of SMK N 1 Karanganyar based on the findings of the problems experienced by teachers and then jointly seek alternative solutions together, so as to form a professional teacher.